(untitled) (Gumilyov Journal of Pedagogy, 2026)
This article presents a theoretical and methodological analysis of the contemporary paradigm of sustainable development and higher education amid the digital revolution. The study traces the transition from rigid academic standards to an ecosystem approach, where the quality of education is inextricably linked to the university’s social contribution and sustainable development goals. In the era of Industry 4.0 and Education 5.0, the quality of education is defined as the university’s mode of existence, which evolves in harmony with the values of sustainable development (ESG), social justice, and responsibility. Viewing the university as an agent of social change, the authors clarify that quality is measured not only by internal KPIs but also by the extent to which graduates and university-led research projects transform society as a complex social system. The article focuses on examining an effective methodology for managing the quality assurance processes of educational programs. Furthermore, it provides a scientific substantiation of the core principles for improving a university’s internal quality assurance system, using a professional teacher training program as a case study.